CXCL1/CXCR2 Paracrine Axis Contributes to Lung Metastasis in Osteosarcoma - Chia-Chia Chao (Cancers, 2020)
Osteosarcoma, the most common of all bone malignancies, has a high likelihood of lung metastasis. Up until now, the molecular mechanisms involved in osteosarcomas with lung metastases are not clearly understood. Recent observations have shown that the chemokine CXCL1 and its receptor CXCR2 assist with the homing of neutrophils into the tumor microenvironment. Here, we show that the CXCL1/CXCR2 paracrine axis is crucial for lung metastasis in osteosarcoma. In an in vivo lung metastasis model of osteosarcoma, lung blood vessels expressed CXCL1 and osteosarcoma cells expressed the CXCR2 receptor. CXCR2 expression was higher in osteosarcoma cell lines than in normal osteoblast cells. Immunohistochemistry staining of clinical osteosarcoma specimens revealed positive correlations between CXCR2 expression and pathology stage and also vascular cell adhesion molecule 1 (VCAM-1) expression. High levels of CXCL1 secreted by human pulmonary artery endothelial cells (HPAECs) promoted osteosarcoma cell mobility, which was mediated by the upregulation of VCAM-1 expression. When HPAECs-conditioned media was incubated in osteosarcoma cells, we observed that the CXCR2 receptor and FAK/PI3K/Akt/NF-κB signaling cascade were required for VCAM-1 expression. Our findings illustrate a molecular mechanism of lung metastasis in osteosarcoma and indicate that CXCL1/CXCR2 is worth targeting in treatment schemas.